Mechanical, compositional, and microstructural changes caused by human skin maceration. (November 2020) - Dhandapani, Niranjana; Samuelsson, Kristin; Sköld, Maria; Zohrevand, Katarina; German, Guy K.
Abstract: We quantify the effects of prolonged exposure to water on the mechanical, compositional and structural degradation of human skin. This environmental exposure is associated with maceration and the pathogenesis of dermatitis, immersion foot syndrome, and trench foot. Uniaxial tensometry reveals that water immersion of isolated stratum corneum (SC) ranging in age across 27 to 87 years can notably stiffen the tissue and cause both reductions in plasticity and rupture energy when allowed to equilibrate to a high relative humidity. Subsequent water sorption studies reveal that water immersion induced decreases in plastic extensibility are caused by a reduction in the tissue's ability to hold water. In turn, this retention decrease is caused by a depletion in both lipids and natural moisturising factors. Further scrutiny of SC mechanical properties further reveals a clear delineation around 70 years. Employing this age-based categorisation, we establish that the degradative impact of water immersion is greatest for SC aged over 70 years. Histological examinations of full-thickness skin further reveal that prolonged water immersion for 7 days causes epidermal delamination, SC cavitation, and degradation in dermal collagen integrity. Immersion of skin in water at colder temperatures however reduces this degradation. Graphical abstract: